Clinical and laboratory spectrum of hereditary angioedema in a group of Egyptian children: a cross sectional study - Mohamed Almalky; Reham M. El Shabrawy; Najeeb Ali Mohammed Gheetah; Hossam Moustafa Elkady; Naglaa S. Osman; Walaa Shoman; Eman Gamal Baz (SpringerOpen, 2024)
Abstract Background Hereditary angioedema (HAE) is a hereditary illness represented by repeated bouts of submucosal or subcutaneous edema. Types of HAE includes; HAE with deficient C1-inhibitor (type 1), HAE with dysfunctional C1-inhibitor (type 2), and HAE with normal C1-inhibitor. Data on the epidemiology of HAE in Egypt are limited. Therefore, we aimed to characterize HAE in Egyptian children, identify the morbidity, and clarify HAE's different clinical and laboratory presentations. Methods In this cross-sectional study, we enrolled pediatric patients diagnosed with HAE according to the international hereditary angioedema WAO/EAACI guidelines. We gathered laboratory data on patients' mean serum C1 esterase inhibitor (C1-INH) level and activity, C4, and IgE levels. Results We included 18 HAE patients (14 females and 4 males). They were between the ages of 6 and 18 years. The mean age upon confirmation of diagnosis was 8.4 ± 2.4 years. The mean time required to correctly diagnose HAE was 3.2 ± 1.8 years. We detected type I in 15 cases and type II in three cases. Eleven patients had a family member with HAE. In terms of previous misdiagnoses, 50% of patients were diagnosed with allergic angioedema. The median annual frequency of episodes was 17. The mean HAE attack time was 2.9 ± 1.5 days. Edema was most typically found in the face and abdomen. Trauma was the main triggering factor. We detected a significant direct relationship between severity of attack and C1-INH activity level. Conclusions This research adds a considerable clinical information about children with HAE. According to current results, there is a considerable underdiagnosis of HAE in Egypt. The detection and management of HAE can be improved by screening the relatives of HAE patients.